The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/tri.12883
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation- and regulation-related patterns in stable hand transplant recipients

Abstract: We assessed cell subsets and expression of a set of genes related to the T-cell populations in peripheral blood mononuclear cells to elucidate whether immune status of stable hand transplant recipients (HTx) differs from stable kidney transplant recipients (KTx). The study was conducted on five HTx 4.8 ± 1.7 years after transplantation and 30 stable KTx 7.9 ± 2.4 years after transplantation as well as 18 healthy volunteers. The research involved PBMC gene expression analysis of CD4, CD8, CTLA4, GZMB, FOXP3, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…We have previously reported that stable hand transplant recipients exhibit persistent immune activation with rejection-related gene expression pattern [42]. Our present study showed that in hand transplant recipients no higher levels of serum inflammatory markers (IFN-γ, IL-I, and IL-6) were observed.…”
Section: Discussionsupporting
confidence: 47%
“…We have previously reported that stable hand transplant recipients exhibit persistent immune activation with rejection-related gene expression pattern [42]. Our present study showed that in hand transplant recipients no higher levels of serum inflammatory markers (IFN-γ, IL-I, and IL-6) were observed.…”
Section: Discussionsupporting
confidence: 47%
“…San Segundo et al [23] observed low levels of Tregs after KTx for six months after transplantation and their recovery to almost basal levels during the first posttransplant year, which may be explained by the high burden of immunosuppression in the early posttransplant period. On the contrary, we previously showed that stable kidney transplant recipients chronically presented lower counts of Tregs compared to controls and stable hand transplant recipients despite their higher immunosuppression load [24]. Moreover, long-term treatment with calcineurin inhibitors in contrast to mTOR inhibitors in stable human renal transplantation was linked to decreased Treg counts [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this latter study, RT patients without a history of cancer post-transplant had similar numbers of Treg to HV, whereas patients with cancer post-transplant had increased CD4 + CD25 + Foxp3 + Treg. A comparison of 30 stable RT patients (mean 8 years post-transplant), 5 hand transplant patients (mean 5 years post-transplant) and 18 HV found that RT patients had fewer CD4 + CD25 + CD127 lo compared to the other groups ( 168 ).…”
Section: Changes In Treg Over Time In Renal Transplant Patientsmentioning
confidence: 99%
“…CD4 + CD25 hi CD127 lo T cells are highly suppressive in vitro ( 166 , 167 ). The CD4 + CD25 hi CD127 lo cells are a functional Treg population in renal transplant patients ( 119 , 126 , 132 , 137 , 154 , 168 , 169 ).…”
Section: Identification Of Treg Population In Peripheral Bloodmentioning
confidence: 99%